Gallstone ileus, controversies on current surgical management - Madrid Ruíz, José Francisco; Hidalgo Artiaga, Karen Elena; Baéz León, Asdrúbal Samuel; Aguilar, José Manuel De Gante; Ora, Omar Maximiliano Ortiz De (International Surgery Journal, 2023)
Among the causes of bowel obstruction, the gallstone ileus represents a rare etiology in the general population, however, the incidence of cases increases in older adults. To make its diagnosis, a high clinical suspicion and extension studies are required. It is considered a surgical emergency, although the ideal approach continues to be debated today. We present the case of a 78-year-old patient with clinical and imaging findings compatible with gallstone ileus, the diagnostic and therapeutic approach, as well as a wide review of the literature about current surgical option.